Effects of Capital and Type of Business on Coastal Muslim Women's Business Income in Aceh Province - Muksal; Arroyyan Ramly; M Shabri Abd Majid; Mirna Indriani (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2020)
This study aims to analyze the influence of capital variables and type of business on the income of Muslim women living in coastal areas in Aceh Province. The population in this study is Coastal Women who do business in Aceh Province by selecting samples using a purposive sampling technique with the criteria that women who do business have a fishing husband, living on the coast in the districts of Nagan Raya, Lhokseumawe and Aceh Besar. Primary data were obtained from interviews and questionnaires with coastal women as many as 90 coastal women doing business. Whereas secondary data was obtained from the Central Statistics Agency (BPS), District Community Empowerment Agency (BPM) and the internet. The analysis first uses the validity and reliability test and then the hypothesis is tested using multiple regression tests to find out whether an independent variable influences the motivation of coastal women with a significance level of 5% which aims to see how the overall relationship between capital and type of business affects women's business income Muslims in Aceh Province. The results show the simultaneous influence of both Capital Variables (X1) and Type of business (X2) significantly influencing Muslim women's Business Income. Based on the regression coefficient of the Capital Variable (X1) and Business Type (X2) partially there is a positive and significant effect on the Coastal Muslim Women's Business Income in Aceh Province. DOI: https://doi.org/10.5281/zenodo.3672387